LGBT DALAM PRESPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Rasfiudin (LPPM-IAI BATAM, 2023)
This study discusses LGBT in the perspective of Islamic law and Indonesian positive law. LGBT (Lesbian, Gay, Bisexual, and Transgender) has become a complex and controversial issue in many countries, including Indonesia. This study aims to analyze how Indonesian Islamic law and positive law view LGBT phenomenon in Indonesia. The research method used is the study of libraries, by collecting and analyzing literature and legal documents related to LGBT in the context of Islamic law and positive Indonesian law. This study analyzed the perspective of Islamic law on LGBT based on principles of Islamic teachings. In addition, this study also analyzed how Indonesia's positive law regulates LGBT, including laws, government regulations, and related court decisions. The results of this study suggest that the perspective of Islamic law on LGBT tends to regard it as a violation of applicable religious values and social norms. Islamic law considers same-sex relationships to be prohibited and includes acts of gross sin. While in positive law and human rights, it does not give room to LGBT. LGBT tendencies are protected under human rights, absolutely not. Because the government can still ban activity and existence with the argument of control and maintenance of moral values. Where LGBT can be seen as abnormal and impinge on the moral damage of the nation's children. So to maintain more positive norms, cultures and moral values, all LGBT activities can be banned by the government.